Assessing Heuristic Bias During Care for Patients Hospitalized for Heart Failure: Get With The Guidelines-Heart Failure. (2nd December 2022) - Selvaraj, Senthil; Greene, Stephen J.; Ayodele, Iyanuoluwa; Alhanti, Brooke; Allen, Larry A.; Lewsey, Sabra C.; Adusumalli, Srinath; Reza, Nosheen; Hernandez, Adrian F.; Yancy, Clyde W.; Jena, Anupam B.; Fonarow, Gregg C.; et al.
Abstract : Background: Heuristic biases are increasingly recognized, and potentially modifiable, contributors to patient care and outcomes. Left digit bias is a cognitive bias where continuous variables are categorized by their left-most digit. The impact of this heuristic bias applied to patient age on quality of care in heart failure has not been explored. Methods: We examined participants admitted from 2005 to 2021 in the Get With The Guidelines-Heart Failure registry. To create 2 naturally randomized groups, isolating the effect of left digit bias, we dichotomized patients into those discharged within 60 days prior to their 80th birthday (N=4238) and those discharged within 60 days after their 80th birthday (N=4329). We performed multivariable logistic regression to assess the association between discharge date relative to 80th birthday and several in-hospital quality metrics and in-hospital outcomes. Among Medicare participants (N=2759), we performed adjusted Cox regression to analyze the relationship between discharge date and risk of 1-year mortality or readmission. Results: Among 8567 patients, 50.4% were female, 73% were non-Hispanic White, and 42.9% had an ejection fraction ≤40%. Discharge date relative to 80th birthday was not associated with numerous in-hospital quality metrics or in-hospital outcomes on unadjusted or adjusted logistic regression. Among Medicare beneficiaries, there was no association between discharge date and risk of mortality or readmission at 1-year postdischarge (hazard ratio, 1.03 [95% CI, 0.95–1.12]; P =0.52). Conclusions: In a large registry of patients hospitalized for heart failure, we did not detect a left digit bias‚ with respect to age at discharge, which resulted in differential quality of care or outcomes.